A numerical investigation on effects of ceiling and floor surface temperatures and room dimensions on the Nusselt number for a floor heating system - Karadag, Refet; Teke, Ismail; Bulut, Huesamettin (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
In this study, the effect of ceiling and, floor surface temperatures and room dimensions on the Nusselt number over the floor of a floor heating system has been investigated numerically. The variation of the Nusselt number with Rayleigh number has been analyzed under constant wall temperature condition for different ceiling temperatures (10-25 degrees C) and room dimensions. It has been seen that when the room dimensions and temperature difference between the ceiling and interior air are increased, the Nusselt number over the floor increases as well. The numerical results have been compared with the correlations given in the literature. It has been seen that the correlations available in the literature are valid only for given thermal conditions and room dimensions. The results calculated from the correlations which do not consider the effects of ceiling and floor surface temperatures deviate up to 35% than the results of this numerical study carried out for different ceiling and floor surface temperatures and room dimensions. Therefore, a new correlation for Nusselt number over the floor, which contain the influence of thermal conditions and all of room dimensions must be discovered. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: floor heating; natural convection; Nusselt number; Rayleigh number; NATURAL-CONVECTION; THERMAL PERFORMANCE; MIXED CONVECTION; DUCT; Thermodynamics; Mechanics